Case report of dissection of the right coronary artery due to uncontrolled rotational movement of the guiding catheter: A twist in the story. Issue 3 (2021) - Dogosh, AlaAbu; Weinstein, Jean Marc; Zahger, Doron; Cafri, Carlos
No abstract available